Thymic Program Directing the Functional Development of γδT17 Cells - Jouan, Youenn; Patin, Emmanuel C.; Hassane, Maya; Si-Tahar, Mustapha; Baranek, Thomas; Paget, Christophe (Frontiers in Immunology, 2018)
γδT cells comprise a unique T cell sublineage endowed with a wide functional repertoire, which allow them to play important - sometimes opposite - roles in many immune responses associated with infection, cancer and inflammatory processes. This is largely dependent on the existence of pre-programmed discrete functional subsets that differentiate within the thymus at specific temporal windows of life. Since they represent a major early source of IL-17A in many models of immune responses, the γδT17 cell population has recently gained considerable interest. Thus, a better dissection of the developmental program of this effector γδT subset appears critical in understanding their associated immune functions. Several recent reports have provided new exciting insights into the developmental mechanisms that control γδT cell lineage commitment and differentiation. Here, we review the importance of thymic cues and intrinsic factors that shape the developmental program of γδT17 cells. We also discuss the potential future areas of research in γδT17 cell development especially in regards to the recently provided data from deep RNA sequencing technology. Pursuing our understanding into this complex mechanism will undoubtedly provide important clues into the biology of this particular T cell sublineage.